2022
DOI: 10.5812/ijem-123560
|View full text |Cite
|
Sign up to set email alerts
|

The G-Protein-Coupled Estrogen Receptor Agonist Prevents Cardiac Lipid Accumulation by Stimulating Cardiac Peroxisome Proliferator-Activated Receptor α: A Preclinical Study in Ovariectomized-Diabetic Rat Model

Abstract: Background: Type 2 diabetes mellitus (T2DM) is associated with cardiometabolic changes, and menopause exacerbates these conditions, leading to a greater risk of cardiovascular diseases (CVDs). The G protein-coupled estrogen receptor (GPER), which mediates the rapid effects of estrogen, has beneficial cardiac effects in both T2DM and menopause, but its mechanism of action is not well understood. Objectives: This study aimed to determine whether G1 as a selective GPER-agonist has beneficial effects on cardiac li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In endothelial cells, oestrogen-mediated activation of GPER attenuates transcytosis of LDL cholesterol into endothelial cells, compatible with an indirect vasculoprotective effect 116 . G-1 also reduces cardiac lipid accumulation and PPARα expression in surgically postmenopausal rats with type 2 diabetes mellitus (T2DM) 117 . In human monocytes, which contribute to the earliest stages of atherogenesis 118 , the anti-inflammatory effects of oestrogen might involve both direct effects via GPER 119 as well as crosstalk between ERα and GPER 120 .…”
Section: Roles Of Gper In Physiology and Diseasementioning
confidence: 99%
“…In endothelial cells, oestrogen-mediated activation of GPER attenuates transcytosis of LDL cholesterol into endothelial cells, compatible with an indirect vasculoprotective effect 116 . G-1 also reduces cardiac lipid accumulation and PPARα expression in surgically postmenopausal rats with type 2 diabetes mellitus (T2DM) 117 . In human monocytes, which contribute to the earliest stages of atherogenesis 118 , the anti-inflammatory effects of oestrogen might involve both direct effects via GPER 119 as well as crosstalk between ERα and GPER 120 .…”
Section: Roles Of Gper In Physiology and Diseasementioning
confidence: 99%
“…Female rats were randomly assigned to five groups (7-10 rats in each group): Sham-Control (Sh-Ctl); T2D; Ovariectomized (OVX)+T2D; OVX+T2D+Vehicle (Veh); and OVX+T2D+G-1. Animals were OVX two weeks before the initiation of experiments as previously described [15]. To induce the T2D model, female rats were given a high-fat diet (HFD) for 8 weeks.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The protective metabolic effects of E2 are traditionally attributed to classical E2 receptors, which are mediated by genomic pathways, a time-consuming and slow process [14]. Recently, increasing evidence has demonstrated that the G protein-coupled estrogen receptor (GPER), as a 7-transmembrane receptor is expressed in a wide variety of tissues such as the heart and blood vessels, and mediates the rapid biological action of E2 [15]. Based on genetic and pharmacological approaches, there is a growing body of literature emphasizing the role of GPER in the regulation of metabolic function of E2 as well as the regulation of cardiac function [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation